Project-led education in engineering: Monitoring and assessing the learning process - Fernandes, Sandra Conceição Carvalho (2007)
This paper presents findings from a case study carried out at the University of Minho, Portugal, with first year Industrial Management and Engineer ing students, who participated in a Project-Led Education (PLE) experience. It emphasizes the importance of formative assessment and the process of providing regular feedback on students’ work as key features to guarantee quality in student learning. Monitoring and assessing the learning process has become an important concern when designing PLE experiences. To meet this goal, a set of milestones are established throughout the project (oral presentations, midterm reports, tutorial meetings, etc.), as well as peer and self-assessment processes, in order to support students in the process of monitoring and regulating their own learning